2020
DOI: 10.1128/aac.00905-20
|View full text |Cite
|
Sign up to set email alerts
|

Caspofungin Weight-Based Dosing Supported by a Population Pharmacokinetic Model in Critically Ill Patients

Abstract: The objective of this study was to develop a population pharmacokinetic model and to determine a dosing regimen for caspofungin in critically ill patients. Nine blood samples were drawn per one dosing occasion. Fifteen patients with (suspected) invasive candidasis had one dosing occasion and five had two dosing occasions measured on day 3 (±1) of treatment. Pmetrics was used for population pharmacokinetic modelling and probability of target attainment (PTA). A target 24-hour AUC value of 98 mg*h/L was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
(68 reference statements)
0
13
0
Order By: Relevance
“…Consequently, the concept of ‘one size fits all’ guiding dosing recommendations of echinocandins seems to be inappropriate in critically ill OLT recipients 44 . This may possibly explain the trend towards higher risk of breakthrough IFI found in our analysis with echinocandins compared to amphotericin B. Echinocandin dosing adjustment (eg anidulafungin 150 mg/day, micafungin 150–200 mg/day or caspofungin 2 mg/kg loading dose followed by 1.25 mg/kg/day 40,42,43 ) should be implemented in critically ill OLT recipients in order to maximise the achievement of optimal PK/PD target especially against Candida spp., representing a major issue in the immediate post‐transplant period 45 …”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Consequently, the concept of ‘one size fits all’ guiding dosing recommendations of echinocandins seems to be inappropriate in critically ill OLT recipients 44 . This may possibly explain the trend towards higher risk of breakthrough IFI found in our analysis with echinocandins compared to amphotericin B. Echinocandin dosing adjustment (eg anidulafungin 150 mg/day, micafungin 150–200 mg/day or caspofungin 2 mg/kg loading dose followed by 1.25 mg/kg/day 40,42,43 ) should be implemented in critically ill OLT recipients in order to maximise the achievement of optimal PK/PD target especially against Candida spp., representing a major issue in the immediate post‐transplant period 45 …”
Section: Discussionmentioning
confidence: 92%
“…Considering that critically ill patients usually exhibit lower serum echinocandin exposure compared to other populations, a more critical and suboptimal concentration are consequently expected in intrabdominal fungal infections. Furthermore, several evidence reported a remarkable echinocandin underexposure both in plasma and surgical site in critically ill patients 40–43 . This may favour the selection of fungi with less echinocandin susceptibility and/or the development of echinocandin resistance 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Weight was one of the most important covariates that may affect the PK parameters of caspofungin. Several previous studies have identified weight as an important covariate that affects CL and V of caspofungin ( 24 , 25 , 29 ). For example, Hall et al ( 29 ) showed that the V and CL of caspofungin increased with an increase in weight.…”
Section: Discussionmentioning
confidence: 99%
“…Würthwein et al ( 30 ) found that the weight was most suitable as a covariate for caspofungin CL and V . Märtson et al ( 25 ) proposed a weight-based dose regimen for caspofungin. However, several other studies ( 26 , 31 33 ) have found no significant effect of weight on the pharmacokinetic parameters of caspofungin, similar to our research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation